(untitled) (Global Journal of Human-Social Science, 2018)
The paper attempts to understand ecofeminism in Indian context which has its genesis in the West. Ecofeminism is the pluralistic theory; it has many voices. After exploring vast body of Indian and Western polemical discourse, the present paper focuses on its basic argument. Many ecofeminists put forth that the patriarchal development attitude is the root cause of the exploitation of women and nature and women are first-hand victims of the exploitation of nature. Embarking on this vital theoretical underpinning of ecofeminism (gender oriented analysis of the environmental crisis), the present paper investigates applicability of ecofeminist discourse in the Indian context by analyzing Indian environmental crisis. Therefore, the hypothesis of the paper to explore is: Are environmental crisis in India gender oriented?.